In vitro evaluation of the wound healing activity of Drypetes klainei stem bark extracts. (4th December 2015) - Brusotti, G.; Andreola, F.; Sferrazza, G.; Grisoli, P.; Merelli, A.; Cuna, F.S. Robustelli della; Calleri, E.; Nicotera, G.; Pierimarchi, P.; Serafino, A.
Abstract: Ethnopharmacological relevance: Drypetes klainei Pierre ex Pax is used in Cameroon by Baka Pygmies in the wound healing process and for the treatment of burns. Aim of the study: To validate the traditional use of D. klainei Pierre ex Pax stem bark extracts through the evaluation of their antimicrobial properties and their ability to improve wound healing process in fibroblast cell cultures. Materials and methods: The antimicrobial properties of D. klainei extracts were evaluated against Staphylococcus aureus ATCC 6538, Streptococcus pyogenes ATCC 19615, Escherichia coli ATCC 10536, Candida albicans ATCC 10231, on the basis of the minimum inhibitory concentration (MIC) and the minimum bactericidal–fungicidal concentration (MBC–MFC) by the macrodilution method. The extracts abilities to accelerate wound healing were studied on murine and human fibroblasts in terms of cell viability and migration (scratch wound-healing assay). Results: All the extracts were non-toxic against the selected microorganisms at the tested concentrations, and significantly improve wound healing process in vitro, compared to untreated controls. However, the defatted methanol extract was active at lower concentrations, compared to the water extract. Conclusions: The ability of both water and defatted methanol extracts to accelerate scratch wound closure in fibroblast cultures may support the traditional use of D. klainei stem bark in the treatment of skin lesions (such as burns) even if no antimicrobial activity was evidenced. Graphical abstract: This study supports the traditional use of D. klainey stem bark in the treatment of skin lesions (such as burns) thanks to the ability of both water (WE) and defatted methanol (DME) extracts to accelerate scratch wound closure in fibroblast cultures